The age of science-tech universities : responsibilities, challenges and strategies /: responsibilities, challenges and strategies. (2021) - Antonietti, Paola Francesca; Bertola, Paola; Capone, Antonio; Colosimo, Bianca Maria; Moscatelli, Davide; Pacchi, Carolina; Ronchi, Stefano
No abstract available